Perkembangan Kawasan Permukiman Akibatnya Terhadap Ruang Terbuka di Kota Semarang - Azzaki, Muhammad Ridha; Soetomo, Sugiono (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Semarang is the capital city of Central Java Province, as a metropolitan city, Semarang has the capablity to support the rapid development of the city , one of the evident is the highly of activity on physical infrastucture, one of them is the construction of residential areas along the high rate of population growth. Settlement area development activities emerge the negatively impact to reduce the existence of open space area. This study uses a quantitative method through positivistic approach. Research data presented by the form of figures and the analysis using the statistics. This study was first carried out in 2006 and 2011 to analyze the spatial through digitized the image map of Semarang, and the results of the digitization of spatial land area of open space and a residential area, which is used to formulate some stage subsequent analysis: 1) Identification and analysis of the influence of the development of residential areas against the open space in the city, 2) Analysis of the acceleration of the projected change of land per year in Semarang in 2006-2020, 3) Analysis of the application of open space 30% (sample in District Tembalang). The result of this analysis showed the relationship between the relevant mutual influence. The rate of population growth and development of residential areas with a relationship of mutual influence supply and demand. Then, as the development of residential areas causes the reduction of open space. In additon, the background of this problem is how to formulate the recommendations to control the land use plan , in order to create an ideal city land use in the future.